NRG1-ErbB Lost in Translation: A New Paradigm for Lung Cancer? - Trombetta, Domenico; Rossi, Antonio; Fabrizio, Federico P.; Sparaneo, A.; Graziano, Paolo; Fazio, Vito M.; Muscarella, Lucia A. (Current Medicinal Chemistry, 2017)
Background: Molecular lesions of the NRG1 gene were recently described as a new molecular feature of Invasive Mucinous Adenocarcinoma of the lung. The NRG1 chimeric ligand leads to aberrant activation of the ErbB2/ErbB3 signaling via PI3K–AKT and MAPK cellular cascades. This review aims to highlight the current knowledge about the ErbB network and the effect of NRG1 deregulation in lung cancer and their merger into the ErbB/PI3K-AKT axis modulation by current pharmacologic strategies. Methods: We performed a structured search of bibliographic databases for peer-reviewed literature to outline the state of the art with regard ErbB signaling deregulation and NRG1 function in lung cancer. The quality of retrieved papers was assessed using standard tools and one hundred thirty-five were included in the review. In many papers the molecular lesions affecting the ErbB receptors in lung cancer but also in other type of solid tumors were updated. Papers describing the physiological role of NRG1 in cells was also screened for the review preparation, as well as the paper reporting NRG1 fusions in lung cancer and their implication in aberrant ErbB pathway activation. Results and Conclusion: Overall, this review highpoints how the knowledge of new molecular mechanisms of ErbB pathway deregulation may help in gaining new insights into the molecular status of lung cancer patients and unveil a novel molecular markers of patients' stratification. Moreover, this ultimately led the selection of new compounds designed to inhibit the bound between Nrg1-ErbB3 as a good alternative way to block the ErbB intracellular signaling.
Keywords: lung cancer